Proposed new interior design for Givi accessories retail at Auto World Building Auto City, Penang. / Ahmad Nashrun Jaafar - Jaafar, Ahmad Nashrun (Faculty of Architecture, Planning and Surveying, 2011)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a proposed new interior design for Givi accessories retail at Auto World building, Auto City world, Penang. With the outcome of selling product and information source of Givi Asia company, it is hope to make Givi Asia get more appreciation because always keep the responsibilities in concerning and care about the safety life and protect the rider when on the road. The concept and image is also apply to both interior and exterior to appeal the centre will be able to lure more customers and visitors who were always keen in our aesthetic values in architecture. There were several researches done to succeed this accessories retail final project, amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the Givi accessories retail demands in terms of function and aesthetic value.